Significance of Bone Marrow Biopsy in Diagnosis of Pediatric Diseases; One Year Experience at a Single Pediatric Hematology/Oncology Center (Medical Forum Monthly, 2024)
Background: Despite the recent advances in the field of hematology in the form of molecular studies and immunophenotyphing, morphological study of bone marrow remains a corner stone in the diagnosis of pediatric hematological diseases. It is also helpful in the diagnosis of many non-hematological diseases. This study is unique in a sense that bone marrow biopsy procedure and morphology reporting were done by a pediatrician trained in clinical hematology.Objective: To describe the indications of bone marrow biopsy and frequency of pediatric hematological and non-hematological diseases on morphological basis.Study Design: Descriptive Case SeriesPlace & Duration of the Study: This study was conducted at the Pediatric Hematology/Oncology Department, The Children Hospital & the Institute of Child Health Multan from January 2010 to December 2010.Materials and Methods: This study was conducted on children whether admitted in hematology / oncology ward or referred from various departments of this hospital. A Performa was filled for each patient including detailed history, clinical examination, base line investigation reports and provisional diagnosis. All bone marrow biopsies were performed from posterior iliac spines according to standard protocol for this procedure. Biopsy samples were stained with Leishman stain for morphological study. Bone marrow biopsy report was issued with detailed morphology, morphological diagnosis and suggestion for further investigations e.g. immunophenotyping. Results: Patients age range was 3 months to 13 years with Male: Female = 1:1. Out of 100 bone marrow biopsy reports , disease distribution was acute lymphoblast leukemia (ALL) 30%, acute myeloid leukemia (AML) 7%, lymphoma infiltration 3%, aplastic anemia 18%, idiopathic thrombocytopenic purpra (ITP) 7%, storage disorders 11%, hemolytic anemia 5%, congenital dyserythropoitic anemia (CDA) 2%, red cell aplasia (RCA) 2%, refractory anemia with excessive blasts (RAEB) 2%, nutritional anemia 3%, malaria 3%, reactive changes 5% and normal morphology 2%.Conclusion: In children, acute leukemia is a leading hematological disease on bone marrow morphology followed by aplastic anemia and various non-hematological diseases. Despite availability of advanced diagnostic facilities, bone marrow biopsy is still a useful diagnostic test in many childhood diseases.